Kesesuaian dan Daya Dukung Ekowisata Pantai di Kabupaten Bantul - Agustina Setyaningrum; Primanda Kiky Widyaputra (Postgraduate Faculty, Yogyakarta Institut of Technology, Indonesia, 2026)
This study aims to analyze the suitability of coastal ecotourism for recreational purposes and to estimate the carrying capacity of coastal areas in Bantul Regency, Indonesia. The research was conducted at four beaches, namely Parangtritis, Parangkusumo, Depok, and Pandansari. The increasing number of tourist visits has created both economic opportunities and environmental pressures, making sustainable management essential. A quantitative descriptive approach was applied using a suitability assessment based on biophysical parameters, including water depth, beach type, beach width, substrate material, current velocity, slope, water clarity, land cover, hazardous biota, and freshwater availability. The carrying capacity was calculated to determine the maximum number of visitors that can be accommodated without degrading the environment. The results indicate that all beaches fall into the suitable category (S2) for coastal recreational ecotourism, with scores ranging from 51 to 58. The highest carrying capacity was found at Depok Beach (36 visitors/day), followed by Parangtritis, Pandansari, and Parangkusumo. These findings suggest that the coastal areas of Bantul Regency have strong potential for ecotourism development, provided that management strategies incorporate carrying capacity principles to ensure environmental sustainability.